Life-cycle analysis for new energy conversion and storage systems : symposium held November 26-27, 2007, Boston, Massachusetts, USA - Symposium R, "Life-Cycle Analysis (LCA) for New Energy Conversion and Storage Systems (2007 : Boston, Mass.); Fthenakis, Vasilis M., 1951-; Dillon, Anne (Anne Catherine); Savage, Nora F. (New York : Cambridge Univ Pr., 2008)
PSZJBL